Analisis Pendapatan Usaha Kemitraan Ayam Broiler di PT. Ciomas Lampung Tahun 2016 (Studi Kasus di Samsul Arifin Farm, Kabupaten Tulang Bawang, Lampung) - Muhammad Arief Ibrahim Purnomo Sidi; Herawati M; Asek A (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2018)
This study aims to determine the income level of broiler plasma farmers in Samsul Arifin Farm, Tulang Bawang District, Lampung. This research is done by using case study method. The data was collected in November-September 2016. The selection of research sites was done purposively, considering that Samsul Arifin farm is one of the active farms to become PT Ciomas Adisatwa’s plasma. The data collected consists of primary and secondary. The analysis method used is descriptive analysis and income analysis. The results showed that broiler breeders with an average partner system earn a profit per period during the year 2016 amounting to Rp32.661.415,38. The R / C value of broiler farming with a partner system of 1.10, which means that livestock business is profitable. Keywords: Partnerships, Income, RO ratio